A Randomized Double-Blind Placebo-Controlled Phase IIB Trial of Curcumin in Oral Leukoplakia - Kuriakose, Moni Abraham; Ramdas, Kunnambath; Dey, Bindu; Iyer, Subramanya; Rajan, Gunaseelan; Elango, Kalavathy K; Suresh, Amritha; Ravindran, Divya; Kumar, Rajneesh R; R, Prathiba; Ramachandran, Surya; Kumar, Nisha Asok; et al. (Cancer prevention research (Philadelphia, Pa.), 2016)
Oral leukoplakia is a potentially malignant lesion of the oral cavity, for which no effective treatment is available. We investigated the effectiveness of curcumin, a potent inhibitor of NF-κB/COX-2, molecules perturbed in oral carcinogenesis, to treat leukoplakia. Subjects with oral leukoplakia (n = 223) were randomized (1:1 ratio) to receive orally, either 3.6 g/day of curcumin (n = 111) or placebo (n = 112), for 6 months. The primary endpoint was clinical response obtained by bi-dimensional measurement of leukoplakia size at recruitment and 6 months. Histologic response, combined clinical and histologic response, durability and effect of long-term therapy for an additional six months in partial responders, safety and compliance were the secondary endpoints. Clinical response was observed in 75 (67.5%) subjects [95% confidence interval (CI), 58.4-75.6] in the curcumin and 62 (55.3%; 95% CI, 46.1-64.2) in placebo arm (P = 0.03). This response was durable, with 16 of the 18 (88.9%; 95% CI, 67.2-96.9) subjects with complete response in curcumin and 7 of 8 subjects (87.5%) in placebo arm, demonstrating no relapse after 6 months follow-up. Difference in histologic response between curcumin and placebo was not significant (HR, 0.88, 95% CI, 0.45-1.71; P = 0.71). Combined clinical and histologic response assessment indicated a significantly better response with curcumin (HR, 0.50; 95% CI, 0.27-0.92; P = 0.02). Continued therapy, in subjects with partial response at 6 months, did not yield additional benefit. The treatment did not raise any safety concerns. Treatment of oral leukoplakia with curcumin (3.6 g for six months), thus was well tolerated and demonstrated significant and durable clinical response for 6 months. Cancer Prev Res; 9(8); 683-91. ©2016 AACR.